Ultrafast Nonlinear Optical Response in Plasmonic 2D Molybdenum Oxide Nanosheets for Mode‐Locked Pulse Generation. Issue 17 (25th June 2018) - Wang, Weiqi; Yue, Wenjie; Liu, Zhengzheng; Shi, Tongchao; Du, Juan; Leng, Yuxin; Wei, Rongfei; Ye, Yuting; Liu, Chang; Liu, Xiaofeng; Qiu, Jianrong
Abstract: 2D plasmons are of particular interest in the exploration of light–matter interactions in 2D materials. In 2D plasmonic materials, response time (in sub‐picosecond scale) of free carriers is order of magnitude faster than excitonic recombination in semiconductors, making them highly attractive for realizing faster optical switching and modulation in nanoscale devices. However, the small carrier density in gapless 2D plasmonic materials like graphene has strongly limited the strength of light–matter interaction and the operative spectral range. Here, it is shown that in optically activated plasmonic molybdenum oxide (MoO3 ) sheets of atomic thickness, the nonlinear optical (NLO) absorption, characterized by a saturable behavior in the near‐infrared region, is notably enhanced by the plasmon resonance, giving a modulation depth of 34.96%. Ultrafast pump‐probe spectroscopy reveals that the transient photobleaching in plasmonic MoO3 nanosheets associated with the relaxation of hot electrons recovers in a timescale less than 200 femtoseconds (fs). This ultrafast NLO response allows the development of an optical switch based on saturable absorption that enables the generation of mode‐locked laser pulses from a fiber laser operating at 1.0 µm region. The results may have strong implications for the application of 2D plasmonics based on 2D MoO3 in nanophotonics. Abstract : Plasmonic two‐dimensional molybdenum oxide (MoO3 ) nanosheets show a remarkable enhancement in nonlinear optical response benefited from the plasmonic effect. By incorporating the plasmonic MoO3 nanosheet‐based saturable absorber film into a Yb‐doped fiber laser cavity, passive mode‐locked pulse operated near 1 µm with a pulse duration of 130 ps can be produced.